Adhesive behaviour of carbon fibre reinforced plastic panels manufactured using woven and unidirectional tape after ultraviolet laser surface treatment. (March 2018) - Botana-Galvín, Marta; Blanco, Ginesa; González-Rovira, Leandro; Rodríguez, Miguel A; Botana, Francisco J
This paper describes the results obtained when ultraviolet laser treatment was performed as a surface treatment prior to adhesive bonding for two aeronautical carbon fibre-reinforced plastics based on an epoxy resin prepreg. Different laser-processing parameters were employed, and their effect on the surfaces was analysed through morphological characterisation and wettability studies. X-ray photoelectron spectroscopy measurements were performed to determine the cleaning and activation effects of the treatment. The strength of the bonded joint was studied for laser-treated and manually ground samples. Samples processed under the selected laser conditions exhibited better adhesive behaviour than the manually treated samples, thereby suggesting that ultraviolet laser treatment could be used as an alternative method for surface activation of aeronautical composites based on epoxy resins.